2024
DOI: 10.3389/feart.2024.1399806
|View full text |Cite
|
Sign up to set email alerts
|

Thermomechanical coupling seepage in fractured shale under stimulation of supercritical carbon dioxide

Guojun Liu,
Delei Shang,
Peng Chu
et al.

Abstract: As a waterless fracturing fluids for gas shale stimulation with low viscosity and strong diffusibility, supercritical CO2 is promising than the water by avoiding the clay hydration expansion and reducing reservoir damage. The permeability evolution influenced by the changes of the temperature and stress is the key to gas extraction in deep buried shale reservoirs. Thus, the study focuses on the coupling influence of effective stress, temperature, and CO2 adsorption expansion effects on the seepage characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…However, the accurate measurement of shale pore structure remains challenging due to its complex and diverse nature. Previous studies have shown that the nanopore system as a critical factor controlling storage capacity of hydrocarbons and fluid flow in the fracture networks (Liu et al, 2024;2017). The characterization methods of the pore structure of shale mainly include image analysis, fluid injection, and non-material injection (Maex et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…However, the accurate measurement of shale pore structure remains challenging due to its complex and diverse nature. Previous studies have shown that the nanopore system as a critical factor controlling storage capacity of hydrocarbons and fluid flow in the fracture networks (Liu et al, 2024;2017). The characterization methods of the pore structure of shale mainly include image analysis, fluid injection, and non-material injection (Maex et al, 2003).…”
Section: Introductionmentioning
confidence: 99%